Anatomical references for optimizing rotational alignment of the humeral component in total elbow arthroplasty with bone loss - Angelika M. Schwarz; Gloria M. Hohenberger; Ulrike M. Schwarz; Georg Lipnik; Georg Feigl; Michael Plecko (Scientific Reports)
Abstract This in-vitro study sought to characterize a concept for humeral component positioning during Total Elbow Arthroplasty (TEA) with bone defects. One-hundred specimens were analysed focusing a potential side-specific consensus; anatomical and Computed Tomography (CT) agreements; age-, sex- and humeral length-dependent associations. The angle of rotational alignment was defined by measuring the relationship between the flexion-extension axis (FEA) of the elbow joint and the flat posterior surface of the distal humerus (PDH). Three independent observers determined the reliabilities. The intraclass correlation coefficients (ICC), Pearson correlation coefficients (r), t-tests (r, p), and levels of 95% confidence interval were computed. P-values (p) were set with 0.05. An average internal rotation angle of the FEA to the PDH from 13.0° (range 6.4–27.1) was specified. Anatomical and CT measurements exposed strong agreements (r = .923, p < .001) and excellent observer agreements (ICCs > 0.900). A contralateral side consensus (r = .906, p < .001) and a statistically significant sex difference (at mean: female: 15.1° versus male: 11.5°; p < .001) was verified. No age- and humeral length-dependent correlations were observed (r < .300). Knowledge of these anatomical landmarks and their spatial relationships can provide an essential reference for surgeons striving to replicate native joint alignment. Additionally, assessment of the contralateral (uninjured) side via CT imaging may offer a valuable template and should be considered in the management of complex TEA cases.